European Society of Paediatric Radiology abdominal imaging task force recommendations in paediatric uroradiology, part IX: Imaging in anorectal and cloacal malformation, imaging in childhood ovarian torsion, and efforts in standardising paediatric uroradiology terminology. - Riccabona, Michael; Lobo, Maria-Luisa; Ording-Muller, Lil-Sofie; Thomas Augdal, A.; Fred Avni, E.; Blickman, Johan; Bruno, Constanza; Damasio, Beatrice; Darge, Kassa; Ntoulia, Akaterina; Papadopoulou, Frederica; Vivier, Pierre-Hugues (Pediatric Radiology, 2017)
At the occasion of the European Society of Paediatric Radiology (ESPR) annual meeting 2015 in Graz, Austria, the newly termed ESPR abdominal (gastrointestinal and genitourinary) imaging task force set out to complete the suggestions for paediatric urogenital imaging and procedural recommendations. Some of the last missing topics were addressed and proposals on imaging of children with anorectal and cloacal malformations and suspected ovarian torsion were issued after intense discussions and a consensus finding process that considered all evidence. Additionally, the terminology was adapted to fit new developments introducing the term pelvicalyceal dilatation/distension (PCD) instead of the sometimes misunderstood hydronephrosis. The present state of paediatric urogenital radiology was discussed in a dedicated minisymposium, including an attempt to adapt terminology to create a standardised glossary.